The Impact of Seasonal Differences on Fish Species Diversity, Price Fluctuations, and Fishermen Welfare on Baron Beach Gunung Kidul - Anggara, David Safri; Rudin, Nur Ahmad (Proceeding International Conference on Science and Engineering, 2020)
Gunungkidul Regency has 73 km of coastline and potential to be developed as center of economic growth based on the utilization of marine fisheries resources. Baron Beach is one of the tourism destination, also has function for fish auction (TPI) and market that caught by fishermen. Seasonal differences affect the conditions of tides and have impact on fishing activities. This makes important for conducted this research. Therefore, this study was conducted to determine the effect of seasonal differences on diversity of fish species and welfare of fishermen on Baron Beach. This research is a qualitative descriptive and was carried out with observation and in-depth interviews with traders, fishermen, and consumers. Data analysis was performed using the Miles and Hubberman methods. The results showed the harvest season occurred in the transition season and mid-rain on October until January. The diversity of fish species at most in this season are Euthynnus affinis, Elagatis bipinnulata, Katsuwonus pelamis, Scomberomorus sp. and Selar crumenophthalmus. Diversity at most on the rainy season is Pampus argenteus, while in the dry season are Stolephorus sp., Elagatis bipinnulata, and Auxis rochei. The method of selling fish was done through fishermen, brought to the fish auction to bought by collectors, traders, and consumers. The selling price of fish on traders and collectors has doubled from the fishermen. The abundance of crops has an impact on welfare of fishermen, consumers and traders. The harvest season also has positive impact on social, tourism and culture. The conclusion from this study is the seasonality affects to diversity of fish species, selling price is relatively stable, and has positive impact on society in terms of economic, social, cultural and tourism.